2019
DOI: 10.3390/medicina55070349
|View full text |Cite
|
Sign up to set email alerts
|

Arabinoxylan-Based Particles: In Vitro Antioxidant Capacity and Cytotoxicity on a Human Colon Cell Line

Abstract: Background and objectives: Arabinoxylans (AX) can gel and exhibit antioxidant capacity. Previous studies have demonstrated the potential application of AX microspheres as colon-targeted drug carriers. However, the cytotoxicity of AX gels has not been investigated so far. Therefore, the aim of the present study was to prepare AX-based particles (AXM) by coaxial electrospraying method and to investigate their antioxidant potential and cytotoxicity on human colon cells. Materials and Methods: The gelation of AX w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 68 publications
7
15
0
1
Order By: Relevance
“…AX presented a FA content of 6.72 µg/mg AX, indicating a highly ferulated structure. Similar FA contents ranging from 5.45 to 7.53 µg/mg AX have been previously reported for other AX extracted from DDGS [8,10]. According to the results, the FA content in AX-1 and AX-2 was not affected by the ultrasonic treatment, indicating that the treatment was not able to release the FA residues from the polysaccharide chains.…”
Section: Ft-ir Analysissupporting
confidence: 87%
See 3 more Smart Citations
“…AX presented a FA content of 6.72 µg/mg AX, indicating a highly ferulated structure. Similar FA contents ranging from 5.45 to 7.53 µg/mg AX have been previously reported for other AX extracted from DDGS [8,10]. According to the results, the FA content in AX-1 and AX-2 was not affected by the ultrasonic treatment, indicating that the treatment was not able to release the FA residues from the polysaccharide chains.…”
Section: Ft-ir Analysissupporting
confidence: 87%
“…AX samples were recorded on a Nicolet iS50 FT-IR spectrometer (Thermo Fisher Scientific Inc., Waltham, MA, USA) in absorbance mode from 400 to 4000 cm −1 range at 20 • C. Thirty-two scans at a resolution of 4 cm −1 were averaged and referenced against air [8].…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the polysaccharides still had a relatively high Mw; in this regard, the Mw the AXs did not seem to impact their antioxidant activity. The antioxidant capacity values obtained for the AXs and FAXs are in the range reported for other AXs from DDGS (12-68 mmol TEAC/kg) [17,38] and higher than those reported in AXs from other maize co-products (6-16 mmol TEAC/kg) [14,39]. The results suggested that AXs and FAXs have great potential as free-radical scavengers in the food, pharmaceutical, medical, and cosmetic industries, The TEAC values of AXs and FAXs are shown in Table 3, as determined by the procedures using DPPH and ABTS solutions.…”
Section: Ax and Fax Gelling And Antioxidant Propertiessupporting
confidence: 65%